Preliminary study on the tea dust explosion: the effect of tea dust size - Nur Hikmah, Semawi; Siti Zubaidah, Sulaiman; Noor Sabrina, Ahmad Mutamim; Siti Kholijah, Abdul Mudalip; Rohaida, Che Man; Shalyda, Md Shaarani; Zatul Iffah, Mohd Arshad; Hayder, A. Abdubari; Rafiziana, Md. Kasmani (EDP Sciences, 2019)
Food-based dust is considered as combustible dust as they composed of distinct particles, regardless of the size or chemical composition and when suspended in air or any other oxidizing medium over a range of concentrations will present a fire or deflagration hazard. The explosion effect from food-based dust can cause catastrophic consequences because the initial shock wave from the explosion lift up more dust and triggers a chain reaction through the plant. One of the parameters that can enhance the explosion is the particle size of the dust. In this study, the effect of four different particle sizes of tea dust on the dust explosion severity was tested in a confined 20 L explosion bomb. Tea dust tends to explode due to its molecular structure which contains a carbon-hydrogen bond that can release the significant amount of thermal energy. The experimental results showed that the values of Pmax and (dP/dt)max of tea dust were more severe for the particle size of 160 ?m for which are 1.97 bar and 4.97 bar/s before drying and 2.09 bar and 7.01 bar/s after drying process. The finer dust reacted more violently than coarser ones. As particle size decreases, the rate of explosion pressure change increases, as long as the size is capable of supporting combustion.